A Comparison of Science Education between Germany, China and Indonesia - Ardi, Ardi; Ananda, Azwar; Rusdinal, Rusdinal; Giastituati, Nurhizrah; Hervi, Fauziah (JURNAL EKSAKTA PENDIDIKAN (JEP), 2024)
The development of a science-based society is strongly influenced by science education. The comparison of science education between Germany, China and Indonesia is an interesting topic because they have different traditions and approaches to developing their science education systems. This research aims to study the differences in science education in Germany, China and Indonesia. This research will compare science education between the three countries through several aspects, such as curriculum, teaching methods, teacher training, educational infrastructure, challenges and opportunities, and philosophical basis. The secondary data used in this research is obtained from reliable sources. The results show that the science education system in Germany is highly organised and focuses on an in-depth understanding of concepts. In contrast, science education in China is highly competitive, and academic achievement is prioritised. Science education in Indonesia tries to combine concept understanding and practical skills. However, implementation and assessment still need to be improved. Thus, a comparison of science education in Germany, China and Indonesia shows differences in curriculum, teaching methods, teacher training, educational infrastructure, opportunity challenges and philosophical basis. Each country has advantages and disadvantages. By thoroughly understanding science education in these countries, we can find many lessons that can be used to improve the science education system. Collaborative efforts and exchange of experiences between these countries will help improve science education.